Ovarian cryopreservation for children aged 3 years or younger: A report of three cases. Issue 10 (10th August 2020) - Kasei, Ryo; Morimune, Aina; Kimura, Fuminori; Kitazawa, Jun; Hanada, Tetsuro; Murakami, Takashi
Abstract: Ovarian tissue cryopreservation has recently been performed as an option for fertility preservation in prepubertal girls with cancer. In this study, ovarian tissue was cryopreserved from 3 girls of 3 years of age or younger during a 3‐year period at our institution. Case 1 was a 1‐year‐old girl, who was diagnosed with a yolk sac tumor in the sacral region. Case 2 was a 2‐year‐old girl, who was diagnosed with retroperitoneal neuroblastoma. Case 3 was a 3‐year‐old girl, who was diagnosed with cerebellar medulloblastoma. All patients had planned to undergo chemotherapy that would affect the ovarian reserve. Because these patients were toddlers, consideration of ethics, the surgical procedure and postoperative management, and optimal method for freezing ovarian tissue was necessary, although gynecologists rarely experience these challenges in daily clinical practice. We herein present the clinical course of these three cases and discuss the peculiarities and countermeasures of ovarian cryopreservation in children.